MORAL VALUES IN FIVE STORY SHORT STORIES: KISAH-KISAH MENJADI DEWASA BY DESI ANWAR AS AN ALTERNATIVE FOR CLASS XI TEACHING MATERIAL: NILAI MORAL DALAM CERPEN LIMA CERITA: KISAH-KISAH MENJADI DEWASA KARYA DESI ANWAR SEBAGAI ALTERNATIF BAHAN AJAR KELAS XI - Alya Rahayu Pratiwi; Rina Ratih Sri Sudaryani (Jurnal Kata, 2024)
This research was motivated by data regarding moral values ​​in the short story collection Lima Stories: Kisah-Kisah Menjadi Dewasa by Desi Anwar as an effort to improve moral values ​​in life. This research aims to: (1) describe the manifestation of moral values ​​in the short story collection Lima Stories: Kisah-Kisah Menjadi Dewasa by Desi Anwar and (2) describe moral values ​​and their relationship to literature teaching in class XI high school. The data source is the short story Lima Stories: Kisah-Kisah Menjadi Dewasa by Desi Anwar (PT Gramedia, 2019). Data collection methods use reading, note-taking and bibliography techniques. The research results show that there are three forms of moral values, namely (1) human relationships with God (5 data), with themselves (13 data), and with other people (15 data). (2) moral values ​​and their relation to teaching literature in class XI SMA are fulfilled from three aspects, namely language, psychology and cultural background. The moral values ​​contained in this short story emphasize aspects of human relationships with other humans.